DEFICIENCY OF LEGISLATIVE SHAPING OF THE CONSENT OF A VICTIM IN HUMAN TRAFFICKING: IS PROSTITUTION PROHIBITED BY PALERMO PROTOCOL? - Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The writer deals in his work with the issue of the consent of a victim to sexual and labor exploitation under the provisions of the Protocol on the Suppression and Punishment of Trafficking in Persons, especially Women and Children on the UN Convention on Transnational Organized Crime. By analyzing preliminary assumptions on which the majority of science stand for, according to which it is possible for a passive subject to consents to its own sexual and labor exploitation, the author finds that the legislative and technical shaping of the relevant provisions of the Protocol is not satisfied concerning this matter. Equalization of all provided manners or instruments of perpetration of criminal offence of human trafficking has brought about a logical error. It is not possible to make equal the effect of coercion and deceit with the effect of providing or accepting the benefits as manners of perpetration of criminal offence of human trafficking on people consent. The first two, if used for sexual exploitation lead to rape instead to human trafficking, which represents a legal-dogmatic obstacle to such legislative-technical approach to the Protocol. The second one can lead to human trafficking according to what is given as a provision of this criminal offence, but the writer also complains about decision from the point of a criminal policy. When it comes to sexual exploitation, such legislative-technical approach along with the consent of the victim covers classical prostitution, and when it comes to labor exploitation the award replaces it as a key mechanism for the regulation of economic relations in ordinary labor markets, with the criminal justice coercion.